2022
DOI: 10.3389/fimmu.2022.826943
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Purinergic Signaling in Heart Transplantation

Abstract: Heart transplantation remains the optimal treatment option for patients with end-stage heart disease. Growing evidence demonstrates that purinergic signals mediated by purine nucleotides and nucleosides play vital roles in heart transplantation, especially in the era of ischemia-reperfusion injury (IRI) and allograft rejection. Purinergic signaling consists of extracellular nucleotides and nucleosides, ecto-enzymes, and cell surface receptors; it participates in the regulation of many physiological and patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 155 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…In addition, the study did not enroll any participants with a history of any clinically important disease, such as cardiovascular disease, who may be of most benefit from AZD3366 therapy. In particular, patients with acute cardiovascular events and ischemia are likely to exhibit higher levels of extracellular tissue ATP and ADP, 23 and the effects of AZD3366 might influence these levels differently when compared with circulating plasma levels in healthy subjects. Therefore, it was not possible to test the tissue‐protective and anti‐inflammatory mode of action of this compound as confirmatory data can be collected only during a phase 2 proof‐of‐concept study in patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study did not enroll any participants with a history of any clinically important disease, such as cardiovascular disease, who may be of most benefit from AZD3366 therapy. In particular, patients with acute cardiovascular events and ischemia are likely to exhibit higher levels of extracellular tissue ATP and ADP, 23 and the effects of AZD3366 might influence these levels differently when compared with circulating plasma levels in healthy subjects. Therefore, it was not possible to test the tissue‐protective and anti‐inflammatory mode of action of this compound as confirmatory data can be collected only during a phase 2 proof‐of‐concept study in patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…33 ATP is generally located inside cells and is an important component of DAMPs. Extracellular ATP participates in purinergic signaling and inflammatory response and is closely associated with diseases such as tumors, ischemic injury, post-heart transplantation, and rejection reactions 34,35 Innate and adaptive immunity are also activated by ATP through a series of reactions. 36,37 Karen M Dwyer's team found that blocking CD39 and CD73 is beneficial for the treatment of acute and chronic kidney diseases.…”
mentioning
confidence: 99%